Behavioural pattern separation is strongly associated with familiarity-based decisions. Issue 3 (15th March 2020) - Szőllősi, Ágnes; Bencze, Dorottya; Racsmány, Mihály
ABSTRACT: Pattern separation is the process that minimises interference between memory representations with similar features and is suggested to be associated with hippocampus-related recollection. We tested this hypothesis using the incidental Mnemonic Similarity Task with old (target), similar (lure), and new (foil) items presented on a recognition test, which is widely used for detecting individual differences in behavioural pattern separation performance. In Experiment 1, participants made old/similar/new decisions and rated decision confidence on a scale ranging from "not at all sure" to "very sure". In Experiment 2, participants made recognition confidence judgments on a scale ranging between "sure it was new" and "sure it was old". In Experiment 3, subjects gave old/similar/new decisions and made a secondary Remember/Know/Guess judgment. In Experiment 1, confidence ratings were higher for targets compared to lures when we analysed correct responses (old for targets and similar for lures). Additionally, we found a symmetrical ROC curve and a linear zROC curve for target-lure discrimination in Experiment 2. Finally, we found a bias toward Know responses when we analysed behavioural pattern separation performance (i.e., the rate of similar responses given to the lures). These findings suggest that familiarity, rather than recollection, contributes to behavioural pattern separation performance.